Media coverage of different scientific disciplines in the Croatian daily press : socio-historical perspective - Šuljok, Adrijana (Array, 2020)
The goal of this research was to determine the changes in frequency and characteristics of media reporting of different scientific disciplines in the socio-historical context in which they arise. The research was conducted using the method of content analysis, which comprised Croatian daily newspapers with the highest readership in two time periods: ’socialism‘, from 1986 to 1988, and ’democracy‘, from 2006 to 2008. The constructed week method was used to select a total of 885 articles. The findings confirm the specificities in media communication of particular scientific disciplines in different socio-political contexts, as well as a tendency of levelling media practices in line with global trends, such as growing orientation towards medicalisation and socio-spatial domination of 'Western' news.